Pre‐ischemic renal lavage protects against renal ischemia‐reperfusion injury by attenuation of local and systemic inflammatory responses. Issue 12 (21st October 2020) - Guo, Shuiming; Zhang, Fuxiang; Chen, Ying; Chen, Yuetao; Shushakova, Nelli; Yao, Ying; Zeng, Rui; Li, Junhua; Lu, Xia; Chen, Rongjun; Haller, Hermann; Gueler, Faikah; et al.
Abstract: Postischemic acute kidney injury (AKI) is a common clinical complication and often fatal, with no effective treatment available. Little is known about the role of leukocytes trapped in renal vessels during ischemia‐reperfusion injury (IRI) in the postischemic AKI. We designed a new animal model in rats with preforming renal artery lavage prior to IRI to investigate the effect of diminishing the residual circulating leukocytes on kidney damage and inflammation. Moreover, the functional changes of macrophages in hypoxia reoxygenation condition were also analyzed. We found pre‐ischemic renal lavage significantly decreased the serum creatinine and blood urea nitrogen levels, and downregulated the mRNA and protein expressions in kidneys and urinary secretion of kidney injury molecule‐1 of rats after IRI. The renal pathological damage caused by IRI was also ameliorated by pre‐ischemic renal lavage, as evidenced by fewer cast formation, diminished morphological signs of AKI in the tissue at 24 hours after IRI. Pre‐ischemic renal lavage reduced the numbers of infiltrating CD68 + macrophages and MPO + neutrophils. The mRNA expression of pro‐inflammatory mediator in IRI kidneys and the levels of pro‐inflammatory cytokines in circulatory system and urine were also reduced due to pre‐ischemic lavage. Compared with nontreated rats with IRI, pre‐ischemic renal lavage significantly reduced the phosphorylation levels of ERK and p65 subunit of NF‐κB in the kidney after IRI. In addition, we found hypoxia/reoxygenation could promote the expression of pro‐inflammatory mediators and inhibit the expression of anti‐inflammatory factors by regulating ERK/NF‐κB signaling pathway. Thus, pre‐ischemic renal lavage could clearly reduce the renal damage after IRI by attenuating inflammation, and macrophages trapped in renal vessels during IRI could be important pathogenic factors driving tissue injury.